Socio-economic Study of Small Farmers of Jammu and Kashmir - Parveen Kumar and M. S. Nain, (Indian Journal of Extension Education, 2013)
The present study was conducted in Jammu and Kathua districts of Jammu and Kashmir. From each district, three villageswere selected randomly. Thus, a total of six villages were selected. A study was carried out prior to the research study toknow about the major crops grown for food grains, livestock and the availability of water for irrigation. Wheat and paddyconstitute the major crops grown in these villages. Potato is also cultivated by limited number of families. Barseem isgrown for live - stock and mustard is also grown by some respondents. Almost the entire area is irrigated. From eachselected village fifteen respondents were selected purposively. The selection of respondents was on the basis of their sizeof land holdings. Farmers having land holdings up to 2 hectares were selected. The final sample, thus consisted of 90respondents. Data was obtained by a well prepared semi-structured interview schedule, which also consisted of a set ofeight statements related to non adoption of technology. The huge yield gap between the yields obtained and the maximumobtainable yields have to be narrowed. There is a considerable potential to increase production and yield per hectare by theintroduction of new inputs and improved practices of cultivation.